Effect of diazoxide on Friedreich ataxia models. (8th January 2018) - Santoro, Antonella; Anjomani Virmouni, Sara; Paradies, Eleonora; Villalobos Coa, Valentina L; Al-Mahdawi, Sahar; Khoo, Mee; Porcelli, Vito; Vozza, Angelo; Perrone, Mara; Denora, Nunzio; Taroni, Franco; Merla, Giuseppe; et al.
Abstract: Friedreich ataxia (FRDA) is an inherited recessive disorder caused by a deficiency in the mitochondrial protein frataxin. There is currently no effective treatment for FRDA available, especially for neurological deficits. In this study, we tested diazoxide, a drug commonly used as vasodilator in the treatment of acute hypertension, on cellular and animal models of FRDA. We first showed that diazoxide increases frataxin protein levels in FRDA lymphoblastoid cell lines, via the mammalian target of rapamycin (mTOR) pathway. We then explored the potential therapeutic effect of diazoxide in frataxin-deficient transgenic YG8sR mice and we found that prolonged oral administration of 3 mpk/d diazoxide was found to be safe, but produced variable effects concerning efficacy. YG8sR mice showed improved beam walk coordination abilities and footprint stride patterns, but a generally reduced locomotor activity. Moreover, they showed significantly increased frataxin expression, improved aconitase activity, and decreased protein oxidation in cerebellum and brain mitochondrial tissue extracts. Further studies are needed before this drug should be considered for FRDA clinical trials.